Analisis Produk Unggulan Pd. Kopi Kuda Bandar Lampung - Andy Fitriyadi Dharma Tilaar (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2022)
occurred in the coffee product of PD Kopi Kuda which is a Micro, Small and Medium Enterprises (UMKM) based company that sells its products but is hampered because the product design it directs has misinterpreted data for that further research is carried out with a descriptive approach to solve the problem of selling packaged coffee by utilizing secondary data that is arranged in a simple way to make it easier to map products that can be said to be superior products. For this reason, this study further examines the products made so that they can be absorbed by the market quickly, this is useful for improving the existing production system, and changing the company's perspective to be more objective. Based on the results of the study, it was found that economical products have more sales advantages because they are easily absorbed by the market. Products with small packaging require further modification of the packaging, and further research is needed for super and medium products because they have many weaknesses in this product, this is due to the high returns.